2022
DOI: 10.7150/thno.70721
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress of carbon dots in targeted bioimaging and cancer therapy

Abstract: Carbon dots (CDs), as one new class of carbon nanomaterials with various structure and extraordinary physicochemical properties, have attracted tremendous interest for their potential applications in tumor theranostics, especially in targeted bioimaging and therapy. In these areas, CDs and its derivatives have been employed as highly efficient imaging agent for photoluminescence bioimaging of tumors cells. With unique structure, optical and/or dose attention properties, CDs have been harnessed in various nanot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 199 publications
0
48
0
Order By: Relevance
“…With these outstanding bio-imaging results, CDs show considerable promise for the clinical diagnosis of cancer. An extensive survey by a group of reviewers [ 92 ] revealed that use of CDs in the clinical setting showed they performed exceptionally well for directing precision surgery for papillary thyroid cancer. Researchers assessed the use of CDs as lymphatic tracers in their reports when doing bilateral and complete thyroidectomies for papillary thyroid cancer.…”
Section: Cds As Cancer Bio-imaging Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…With these outstanding bio-imaging results, CDs show considerable promise for the clinical diagnosis of cancer. An extensive survey by a group of reviewers [ 92 ] revealed that use of CDs in the clinical setting showed they performed exceptionally well for directing precision surgery for papillary thyroid cancer. Researchers assessed the use of CDs as lymphatic tracers in their reports when doing bilateral and complete thyroidectomies for papillary thyroid cancer.…”
Section: Cds As Cancer Bio-imaging Agentsmentioning
confidence: 99%
“…The associated results demonstrated that the CDs can clearly identify the Central District lymph nodes and separate thyroid tissue from the surrounding lymphoid adipose tissue, hence lowering the risk of parathyroid gland injury during thyroid cancer. As a result, the research has validated the ability of CDs to achieve targeted cancer bioimaging and approved their tremendous potential for clinic applications in the future [ 92 ]. Table 2 summarizes some examples of precursors, technique, size, and the quantum yield of various CDs.…”
Section: Cds As Cancer Bio-imaging Agentsmentioning
confidence: 99%
“…In recent years, great success has been achieved in the application of various carbon nanomaterials in different gynecologic cancers including ovarian, cervical, and endometrial cancers. Although many overviews have summarized the progress of carbon-based materials as the nano platform for the detection and therapy of cancer-related diseases [ 24 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ], few reviews have paid attention to the achievements in the theranostics of gynecologic cancers with carbon-based nanomedicines. In view of the rapid development and progress in this field in the past five years, this review comprehensively summarizes the latest progress in the application of various carbon nanomaterials (e.g., mesoporous carbon, graphenes/nanotubes, carbon nanoparticles, carbon dots, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…27 To date, the widely used carbon-based nanomaterials have been extensively and deeply explored in the field of bone regeneration. [28][29][30][31][32] However, reviews on CDs are still focused on biosensing, bioimaging and related fields; [33][34][35][36][37] a more focused overview of their applications in BTE is still lacking. Therefore, a systematic review of CDs with osteogenic-activity-related factors in the field of BTE may open up new research directions, which is of great significance to the selection of new biomaterials for bone regeneration.…”
Section: Introductionmentioning
confidence: 99%